Psychiatric epidemiology searching for the causes of mental disorders - Susser, Ezra S., 1952- (New York ; Oxford : Oxford University Press, 2006)
Starting out by tracing the brief history of psychiatric epidemiology, this text describes the study of risk factors as causes of mental disorders. Subsequent sections discuss approaches to investigation of biologic, genetic or social causes and the statistical analysis of study results.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psychiatric epidemiology; Mental illness -- Etiology